PENGARUH GAYA KEPEMIMPINAN DAN STRES KERJA TERHADAP KEPUASAN KERJA DENGAN SEMANGAT KERJA SEBAGAI VARIABEL INTERVENING PADA PT. DUWA ATMIMUDA KUDUS - Ayuningsih, Ayu Putri; Supriyono, Supriyono -; Fahira, Keke Tamara (Jurnal Studi Manajemen Bisnis, 2024)
This study aims to analyze the influence of leadership style and work stress on job satisfaction with work spirit as an intervening variable at PT. Duwa Atmimuda Kudus. The population in this study were all employess of PT. Duwa Atmimuda Kudus has 304 employees. The sampling technique in this research used a purposive sampling technique consisting of 173 respondens. The data analysis used is SEM operated though the AMOS 24 program. The results of this study show that leadership style has a positive and significant effect on work morale, work stress has a positive and significant effect on work morale, leadership style has positive and significant effect on job satisfaction, work stress has a positive and significant effect on job satisfaction, and work spirit has a positive and significant effect on job satisfaction.Keywords: leadership style, work stress, job satisfaction, work spirit